2018
DOI: 10.1016/j.electacta.2018.06.187
|View full text |Cite
|
Sign up to set email alerts
|

Effective particle dispersion via high-shear mixing of the electrolyte for electroplating a nickel-molybdenum disulphide composite

Abstract: The hydrophobic nature of molybdenum disulphide (MoS2) particles is a major challenge for electrodepositing uniform Ni-MoS2 composite coatings due to particle agglomerates present in the aqueous nickel plating bath. In this study, high-shear mixing was shown for the first time as a facile and effective way to achieve a narrow particle-size distribution and stable particle dispersions in the electrolyte, which were characterised by measuring particle-size distributions via dynamic light scattering. The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…Since nanosized particles, such as WS2 and WC, are electrically conductive, the nickel ions can be reduced both on the nickel deposits and on the surface of nanoparticles. This growth mechanism has been investigated and described in the previous studies, such as Co/WS2 [30], Ni/WS2 [20,24], Ni/WC [29,31], Ni/P/WS2 [26] and Ni/MoS2 [25]. In this study, we found the surface morphology closely depended on the type and concentration of nanoparticles.…”
Section: Surface Morphologies Roughness and Wettabilitysupporting
confidence: 61%
See 2 more Smart Citations
“…Since nanosized particles, such as WS2 and WC, are electrically conductive, the nickel ions can be reduced both on the nickel deposits and on the surface of nanoparticles. This growth mechanism has been investigated and described in the previous studies, such as Co/WS2 [30], Ni/WS2 [20,24], Ni/WC [29,31], Ni/P/WS2 [26] and Ni/MoS2 [25]. In this study, we found the surface morphology closely depended on the type and concentration of nanoparticles.…”
Section: Surface Morphologies Roughness and Wettabilitysupporting
confidence: 61%
“…The WC NPs and WS2 NPs improved abrasive resistance of coatings; the combined effects are discussed below. The mechanism on one type of particle has been considered in our previous studies [20,25,26,28,29]. In addition, the current density of electrodeposition was fixed at 4 A dm -2 to avoid the hydrogen evolution reaction (equation 3) at anode which was harmful to coating.…”
Section: Electrodepositing Arrangement and Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al . have stressed the improved deposits achieved by dispersion of particles in electrolyte using high shear mixing, rather than the commonly used magnetic stirring . The importance of this approach is illustrated in Fig.…”
Section: Applicationsmentioning
confidence: 99%
“…Zhou et al have stressed the improved deposits achieved by dispersion of particles in electrolyte using high shear mixing, rather than the commonly used magnetic stirring. 59 The importance wileyonlinelibrary.com/jctb of this approach is illustrated in Fig. 18, where the quality of electrolyte dispersion and deposit performance is considered for Ni-MoS 2 electrodeposits.…”
Section: Coatings and Surface Finishesmentioning
confidence: 99%